The Impact of the COVID-19 Pandemic on the Financial Performance of Commercial Banks - Abadi, Ruklie; Purwanti, Ika (STAI Denpasar Bali, 2023)
This study aims to investigate the impact of the COVID-19 pandemic on the financial performance of commercial banks through a comparative analysis. The research model adopts a qualitative approach to delve into the nuanced factors affecting bank performance during the pandemic. Purposive sampling is employed to select participants from the commercial banking sector. Data analysis involves thematic coding and comparative analysis. Findings reveal insights into the resilience and adaptability of commercial banks amidst the pandemic, shedding light on key indicators such as capital asset ratio, return on assets, operational costs, and liquidity ratios. The study contributes to understanding how commercial banks navigate financial challenges during crises, providing valuable insights for stakeholders and policymakers.